INFLUENCE OF ORGANIC FERTILIZER ON DATE PALM CV. BARHI 2. LEAVES MINERAL CONTENT - & Abood, Taha (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
This experiment was carried out in a private palm farm located in Great Musayib enacted / Babylon province on Barhi dates palm trees Phoenix dactylifera L. cultivar to determine the effect of spraying of chitosan and soil additives for both organic fertilizers and amino acids and seaweed extract in some leaves mineral content (nitrogen, phosphor, potassium, iron, manganese and zinc) by spraying the chitosan at concentrations of 5 ml. l-1 and 10 ml.L -1 and the addition of both organic fertilizer and amino acids and seaweed extract at concentrations (1, 2) kg.tree -1 and (3 , 6) ml . L - 1 and (4, 8) ml l -1 respectively. Each treatment replicated five times with a factorial experiment using RCBD, one date palm for experimental unit.The following are the main findings, The effect of chitosan spray significantly in the leaves mineral content as the concentration gave at10 ml.L -1 (C2) significantly increased leaves N content of 1.07 %, leaves K content of 1.28 % and leaves zinc content of 22.99 mg.kg-1 dry weight. That spray at levels 8ml.L-1(S2) significantly superiority of the control treatment and gave the highest leaves K content of 1.40 % and leaves Mn content of 1.233 mg.kg-1 dry weight, amino acid at 6 ml. L - 1(A2) treatment gave the highest leaves N content of 1.14 %, leaves P content of 0.180 %, leaves Fe content of 178.6 mg.kg-1 dry weight,. While the lowest results in the control treatment.